Seeds4Liberia Scaling for Impact Report 2024–2025: Advancing Seed System Governance, EGS Production, and Multi Value-Chain Innovation in Liberia - Ndindeng, S.A.; Sanni, L.; Fregene, B. (2025)
The Seeds4Liberia project—Building resilient seed systems for rice, cassava, soybean, coffee, and fish value chains to strengthen food and economic diversification in Liberia— made significant progress during the reporting period, positioning Liberia on a strong pathway toward sustainable seed system transformation. Implemented by AfricaRice (lead), IITA, and WorldFish, and funded by the European Union under the NDICI programme, the project has advanced its core scaling vision: to accelerate adoption of high-performing, climate-resilient, and market-responsive varieties and species through robust public–private seed systems. Guided by CGIAR’s Scaling for Impact (S4I) framework, the project delivered foundational market intelligence, enhanced institutional capacity, initiated large-scale early generation seed (EGS) production, strengthened private sector actors, and operationalised Liberia’s Seed Development and Certification Agency (SDCA). These achievements collectively establish a strong enabling environment for scaling quality seeds and fingerlings across value chains.